Processo rápido de obtenção de pão de forma com adição de extrato flavorizante natural - Bezerra, Luciana Cristina Nogueira de Moraes (2021)
Bread is a product of daily consumption by most people around the world. The biological fermentation enables proper aeration, dough expansion and production of flavouring compouds with a variable time of two to five hours or more. Aiming to decrease production time of loaf bread, we proposed the development of a bread with chemical fermentation and aqueous extract containing compounds of conventional pan bread flavor. The optimization of the production conditions of the bread flavoring extract was conducted through the response surface methodology and used the leaching time and temperature of the matrices as predictor variables and the number and the total area of ​​the chromatographic peaks as response variables. The best formulation was obtained through of the bread quality evaluation by a trained team. The best bread formulation was subjected to physical-chemical analysis (moisture, ash, protein, lipids, carbohydrates and pH), acceptance test (attitude scale) and analysis of volatile. The experimental design used for the optimization of the extracts manufacturing process did not allow to obtain a response surface, but it was possible to identify impact volatiles in the final bread aroma, such as 2-Phenylethanol and 3-Methyl-1-butanol. The best formulation was the one from the bread made with 8.5% of bread flavoring extract, 7.7% baking powder and 5.5% vegetable fat with a total quality score equal to 73.01%. The breads produced in this experiment had a composition in moisture, carbohydrates, proteins and lipids similar to conventional bread with 30,61%, 54.83%, 7.43% and 3.30%, respectively and a higher ash content than conventional bread (3,82%). The acceptance test demonstrated that the evaluators showed the consumption attitude “I would eat it often”. The analysis of the volatiles of fast bread by CG / MS allowed to identify 12 compounds that are part of the flavor of conventional breads. Therefore, we believe in the possibility of making a bread with reduced processing time (< 1,0 hour) and with satisfactory sensory acceptance.